Torsion at thirteen: a case report of paraovarian cyst with ovarian torsion in an adolescent girl - Kashi, Ashwini; R., Sheela S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Paraovarian cysts represent 5-20% of all adnexal masses; identified in 15.7% of patients undergoing operative laparoscopy. It is diagnosed when complications like cyst torsion, rupture, haemorrhage and neoplasm. Ovarian torsion contributes ~2.7% of all acute abdomen in children, as early as 5 years of life. A 13 years old girl came to OBG department with complaints of mild pain abdomen in lower left abdomen. Vitals stable, body mass index (BMI) 33.6 kg/m2. On palpation, mild tenderness noted in the left iliac fossa. Ultrasound showed a paraovarian cyst. Patient attenders were not willing for surgical intervention, patient discharged against medical advice. Patient presented to emergency department 10 days later with complaints of pain abdomen since morning, localised to left lower abdomen with vomiting. History of fever since 5 days, now resolved. Patient vitals-pulse of 102 b/min, blood pressure (BP) 100/70mm of Hg. Biomarkers within normal limits. Ultrasound showed bulky (volume ~110 cc) left ovary with absent vascularity on Doppler; a cystic lesion in left adnexa measuring ~7.1×5.9×6.1 cm (vol ~137 cc) likely paraovarian cyst. She underwent Exploratory laparotomy with left salpingo-oophorectomy with left ovarian cystectomy done. Post-operative period uneventful. Histopathology reported as features consistent with torsion of left ovary with paraovarian cyst. In this case of an adolescent girl, if operative intervention was done at first presentation, isolated left paraovarian cystectomy with fertility sparing surgery. The role of expectant management in paraovarian cyst is being studied. Hence, paraovarian cyst should be considered in differential diagnosis of adnexal mass.